2017
DOI: 10.2169/internalmedicine.56.7573
|View full text |Cite
|
Sign up to set email alerts
|

Development of Extranodal NK/T-cell Lymphoma Nasal Type in Cerebrum Following Epstein-Barr Virus-positive Uveitis

Abstract: A 74-year-old woman developed bilateral uveitis with high Epstein-Barr virus (EBV) DNA load in the vitreous fluid without lymphoma cells. Four years after the onset, T2-weighted contrast-enhanced MRI revealed hyperintense lesions in the right occipital and parietal lobe. A biopsy resulted in the diagnosis of extranodal NK/T-cell lymphoma nasal type (ENKL). The repeat region of LMP1, an EBV gene, detected in the brain lesion was identical to that detected in the vitreous fluid. ENKL of the central nervous syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…Therefore, it is wondered whether the retinitis in this patient was neoplastic. A similar case was reported by Imai et al [ 10 ] that was ultimately observed to have an intraocular natural killer (NK)/T-cell lymphoma. Although several cases of intraocular NK/T-cell lymphoma have been previously reported [ 11 ], such rare EBV-associated NK/T-cell tumors appear to be more likely to involve the orbit or ocular adnexa [ 12 ].…”
Section: Discussionsupporting
confidence: 71%
“…Therefore, it is wondered whether the retinitis in this patient was neoplastic. A similar case was reported by Imai et al [ 10 ] that was ultimately observed to have an intraocular natural killer (NK)/T-cell lymphoma. Although several cases of intraocular NK/T-cell lymphoma have been previously reported [ 11 ], such rare EBV-associated NK/T-cell tumors appear to be more likely to involve the orbit or ocular adnexa [ 12 ].…”
Section: Discussionsupporting
confidence: 71%
“…Therefore, it is wondered that whether the retinitis in this patient was neoplastic. A similar case was reported by Imai et al 10 that was ultimately observed to have an intraocular natural killer (NK)/T-cell lymphoma. Although several cases of intraocular NK/T-cell lymphoma have been previously reported 11 , such rare EBVassociated NK/T-cell tumors appear to be more likely to involve the orbit or ocular adnexa 12 .…”
Section: Discussionsupporting
confidence: 68%
“…than extracranial NK/TCL. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] PCNSLs are often accompanied by nonspecific clinical symptoms such as dizziness, headache, vomiting, and blurred vision. Our patient presented with loss of visual acuity and weakness of the limbs, which were consistent with the nonspecific symptoms of primary CNS lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only 23 cases of PCNS ENK/TCL have been reported in the English literature. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] To date, the understanding of this tumor is not deep enough. Herein, we present a case of PCNS ENK/TCL in a 50year-old immunocompetent Chinese female and review of the literature.…”
Section: Introductionmentioning
confidence: 99%